2019
DOI: 10.14309/ajg.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Response in Chronic Idiopathic Constipation: A Systematic Review and Meta-Analysis

Abstract: OBJECTIVES: Chronic idiopathic constipation (CIC), like other functional gastrointestinal disorders, has been associated with a high placebo response rate. However, the placebo response in randomized controlled trials has not been described. METHODS: We conducted a search of the medical literature following the protocol outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis statement using MEDLINE, EMBASE and EMBASE Classic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…The homogeneous result of intergroup difference in the mean PAC-QoL total score and significant reduction of intragroup difference in both questionnaires reflected a strong placebo effect in both treatments. The placebo effect has been systematically described in clinical trials of CIC, with a range from 4 to 44%, 26 which is consistent with results in other functional gastrointestinal diseases. 7 Psychological comorbidity was caused by repeated consultations, unnecessary investigations and impaired health-related quality of life in patients with FC.…”
Section: Discussionsupporting
confidence: 71%
“…The homogeneous result of intergroup difference in the mean PAC-QoL total score and significant reduction of intragroup difference in both questionnaires reflected a strong placebo effect in both treatments. The placebo effect has been systematically described in clinical trials of CIC, with a range from 4 to 44%, 26 which is consistent with results in other functional gastrointestinal diseases. 7 Psychological comorbidity was caused by repeated consultations, unnecessary investigations and impaired health-related quality of life in patients with FC.…”
Section: Discussionsupporting
confidence: 71%
“…It tended, however, to be time-dependently increased in the control group as well as in the probiotics group. Meta-analysis indicated that a placebo increased bowel movement in patients with chronic idiopathic constipation [23] . Another clinical trial also indicated that a placebo increased bowel movement in healthy adults with constipation tendency [19] .…”
Section: Discussionmentioning
confidence: 98%
“…Meta-analysis indicated that a placebo increased bowel movement in patients with chronic idiopathic constipation. [23] Another clinical trial also indicated that a placebo increased bowel movement in healthy adults with constipation tendency. [19] The time-dependent increase of bowel movement frequency may therefore be associated with placebo effects.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, a thorough literature search has shown that there might be a rethink on the use of a few old, relatively inexpensive and effective drugs for CIC patients, such as some magnesium salts, while many others need more accurate and modern investigations before they can be proposed for this purpose. There is little doubt that the pharmacologic approach to the treatment of CIC, despite important advances in drug development [ 11 , 12 ], is still far from an ideal goal [ 8 , 63 ]. Furthermore, patients’ knowledge on this issue is hampered by the poor quality and readability of online information [ 64 ].…”
Section: Discussionmentioning
confidence: 99%